The Impact of Out-of-Home Childcare Centers on Early Childhood Development - Gregory Veramendi; Sergio Urzua (Inter-American Development Bank (IDB), 2011)
This paper presents a comprehensive empirical analysis of the impact of attending a child day care center on early childhood development (ECD) in Chile, examining child development from a multi-dimensional perspective. The potential endogeneity associated with the parental decision of sending children to day care centers (or preschools) is addressed. Additionally, unobserved heterogeneity is interpreted as (latent) abilities. This approach provides a unifying framework combining parental decisions, childrens endowments, and child care characteristics. The results of the study suggest that: (i) cognitive and socioemotional test scores from children younger than two are too noisy to be analyzed; (ii) analysis of enrollment in child care centers for children older than two reveals significant effects of family background, unobserved abilities, the local availability of centers, and local capacity; and (iii) enrollment in child care centers seems to boost cognitive development among children older than two.
Keywords: 330